Pajak Perdagangan Internasional Sebagai Penerimaan Negara - Zefanya Mayvi Ardira; Zaenal Muttaqin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
A country's prosperity is characterized by a stable economy with low or almost no inflation. Strong economic growth relies heavily on a solid financial sector. Taxes are one of the main sources of state revenue which is important to meet economic needs and the government budget. International trade taxes, including import duties on imported goods and export duties on exported goods, are an important source of income for the government, functioning to increase state revenues, protect domestic industry, regulate the flow of goods, and maintain trade balance. Revenues from international trade taxes and import duties experienced quite good growth after a decline in 2020. Export tax revenues experienced a big jump in 2021 and 2022, but decreased again in 2023. This research is an analytical descriptive study that was analyzed qualitatively.